90 YEARS OF CHILDREN HEALTH GUARDING (TO THE 90TH ANNIVERSARY OF SCIENTIFIC RESEARCH INSTITUTE OF CHILDREN’S INFECTIONS) - Yu. V. Lobzin; N. V. Skripchenko; V. M. Volzhanin (Журнал инфектологии)
The article presents the basic aspects of the activity of the institution established for the benefit of children from the moment of its foundation in 1927. There are noted landmarks in history and the priority scientific research works carried out in different periods of the institution development. Some results of the current history, improvement of its material resources are presented. There are described scientific achievements and the institution discoveries and their social value.